Exploring Sadness and Happiness in Rumi’s Masnavi: A Comparative Analysis with Perspectives of Other Thinkers - Ashrafi, Ali (Jurnal Pendidikan Humaniora, 2023)
This research studies the two elements and categories of sadness and happiness in the Masnavi of Jalal al-Din Rumi and compares it with some of the most thoughtful views of the past and today. Considering that Rumi recommends the audience to be happy in Masnavi and other works of his own. It is stated that Rumi has a positive attitude toward happiness and escape from sadness. Happiness is one of the positive human emotions. In different perspectives, it has been identified as a factor in achieving the ideal of knowledge and perfection. On the other hand, Rumi knows the path to God in happiness and sincerity. Among Indian mysticisms, the philosopher Ashou consider heart which has given a great deal of happiness. Freud sees the satisfaction of human instincts as the cause of happiness, and Buddha considers mind and subcategories as a source of happiness and sadness. Rumi's view of this category is regarded as a particular point of view of human experience and intuition is his person. In fact, sadness and happiness are among the most important elements of Rumi's stories. In his view, sadness and happiness are completely interior, not exterior. Therefore, human beings may be at the height of blessings, sad, and, conversely, one in the depths of extreme poverty. Rumi is a loyal and intelligent poet, and sadness from his point of view is an evolutionary development from the lowest to the highest level. According to Rumi's ideas in Masnavi, wisdom sadness must be welcomed and go on with unwise happiness that wise sadness is the path to happiness, dynamism, and mobility of the soul; it destroys many of the sadness and divine happiness s in everyday life.